The Grapes of Wrath Movie Still - Twentieth Century Fox:::Creator::::::::::::
The Joad family debating their future over dinner. Ma Joad (Jane Darwell) and Pa Joad (Russell Simpson) talking while family eats in Twentieth Century Fox's adaptation of John Steinbeck's novel. RESTRICTED USE